Fintech Lending Business Ethics in Indonesia: A Case Study of Shopee Pinjam (SPinjam) - Poppy Wulandari; Maulana Ibrahim (InFestasi, 2023)
Fintech lending plays a significant role in Indonesia as a developing country where the need for loan funds is very high. Although the reason for the significant growth of fintech lending in Indonesia is motivated by the consumerist nature of the Indonesian people in the use of loan funds, the presence of fintech lending has also become a solution in the ease of obtaining loan funds. In Indonesia, fintech lending services are not only available on fintech lending platforms but are also available on e-commerce. This study aims to examine the practice of business ethics in fintech lending services provided by Shopee's collaboration with Lentera Dana Nusantara (LDN), namely SPinjam. This study uses a qualitative research method with a normative juridical approach. The collection of data in this study comes from primary and secondary data sources. In this study, interview results from informants were processed using MAXQDA Standard software to interpret the results systematically. For the sake of the validity of the research results, this study also involved a triangulation approach to check the correctness of the data from information obtained from primary and secondary sources. Even though the results of this study show a tendency for good business ethics from SPinjam, there are still findings indicating that the regulations in SPinjam are not transparent, especially regarding information about the amount of interest charged to users.